Specific recognition of the product of a transferred major histocompatibility complex gene by cytotoxic T lymphocytes. - Woodward, J G (1982)
Mouse L cells transfected with a genomic clone containing the H-2Ld gene (8-5 cells) were shown to function as targets for H-2Ld-specific cytotoxic T lymphocytes (CTL). The CTL-mediated lysis of 8-5 cells was shown to be H-2Ld specific by the use of (i) CTL with restricted reactivity, (ii) unlabeled target inhibiton, and (iii) monoclonal antibody inhibiton. We also demonstrated that 8-5 cells could function as targets for antibody-plus-complement-mediated cell lysis. Specificity was confirmed by using H-2Ld-specific monoclonal antibodies. These experiments demonstrate that the gene products of a major histocompatibility complex genomic clone can be functionally expressed in a foreign cell and can mediate immunologically specific cellular interactions.